The Response of Lentil (Lens culinaris Medik.) to Soil Moisture and Heat Stress Under Different Dates of Sowing and Foliar Application of Micronutrients - Venugopalan, Visha Kumari; Nath, Rajib; Sengupta, Kajal; Nalia, Arpita; Banerjee, Saon; Chandran, Malamal A. Sarath; Ibrahimova, Ulkar; Dessoky, Eldessoky S.; Attia, Attia O.; Hassan, Mohamed M.; Hossain, Akbar (Frontiers in Plant Science, 2021)
Soil moisture and air temperature stress are the two major abiotic factors limiting lentil (Lens culinaris Medik.) growth and productivity in the humid tropics. Field experiments were conducted during winter seasons (November to March) of 2018–2019 and 2019–2020 on clay loam soil (AericHaplaquept) of Eastern India to cultivate rainfed lentil, with residual moisture. The objective was to study the effect of different time of sowing and foliar spray of micronutrients in ameliorating the effect of heat and moisture stress lentil crop experience in its reproductive stage. The study was conducted with two different dates of sowing, November and December, as main plot treatment and micronutrients foliar spray of boron, iron, and zinc either alone or in combination as subplot treatment. No foliar spray treatment was considered as a control. The soil moisture content is depleted from 38 to 18% (sowing to harvest) during November sowing; however, in December sowing, the depletion is from 30 to 15%. The foliar spray of micronutrients helped to have a better canopy cover and thus reduced soil evaporation during the later stages of crop growth when the temperature was beyond the threshold temperature of the crop. Crop growth rate (CGR) and biomass were significantly higher (p ≤ 0.05) for November sown crop and with foliar spray of boron and iron (FSB + FE) micronutrients. In the later stages of the crop when the soil moisture started depleting with no precipitation, the canopy temperature increased compared with air temperature, leading to positive values of Stress Degree Days (SDD) index. Delay in sowing reduced the duration by 11.4 days (113.5 vs. 102.1 days), resulting in varied accumulated Growing Degree Days (GDD). FSB + FE resulted in the highest yield in both years (1,436 and 1,439 kg ha−1). The results of the study concluded that the optimum time of sowing and foliar spray of micronutrients may be helpful to alleviate the soil moisture and heat stress for the sustainability of lentil production in the subtropical region.